China's efforts to contain Renminbi's depreciation and the relating impacts. Issue 1 (2nd January 2019) - Zhang, Ming
ABSTRACT: China began to face Renminbi (RMB) depreciation pressure since 2014Q2, and the 8/11 reform in 2015 exacerbated the RMB depreciation pressure against USD. To contain the depreciation pressure, the People's Bank of China (PBC) adopted three methods. Firstly, PBC tried to stabilize the exchange rate by selling USD and purchasing RMB, which resulted in the fast shrinking of China's foreign exchange reserve. Secondly, PBC strengthened the regulation of capital outflows, which caused the stagnation of RMB internationalization. Thirdly, PBC frequently changed the pricing mechanism of the daily fixing of RMB to USD, which led to the reverse of the liberalization of RMB exchange rate. Under the new environment of RMB depreciation pressure and much lower foreign exchange reserve, Chinese government changed its strategies and became more cautious and pragmatic in outward foreign direct investment, RMB internationalization, and Belt & Road Initiative construction.